2000
DOI: 10.1152/ajpheart.2000.278.6.h1866
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional remodeling of skeletal muscle microvasculature is induced by simulated microgravity

Abstract: Hindlimb unloading of rats results in a diminished ability of skeletal muscle arterioles to constrict in vitro and elevate vascular resistance in vivo. The purpose of the present study was to determine whether alterations in the mechanical environment (i.e., reduced fluid pressure and blood flow) of the vasculature in hindlimb skeletal muscles from 2-wk hindlimb-unloaded (HU) rats induces a structural remodeling of arterial microvessels that may account for these observations. Transverse cross sections were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
164
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(187 citation statements)
references
References 30 publications
20
164
0
2
Order By: Relevance
“…Specifically, absolute vascular conductance was decreased to a greater extent in muscles composed of proportionally more FOG and SO fibres than in their FG-containing counterparts. Consistent with our results, others Delp et al 2000) have shown previously that isolated arterioles from slow twitch muscle (i.e. the soleus) demonstrate a more potent vasodilatation in response to dilators acting through the vascular endotheliuni when compared to the response in isolated arterioles from fast twitch muscle (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, absolute vascular conductance was decreased to a greater extent in muscles composed of proportionally more FOG and SO fibres than in their FG-containing counterparts. Consistent with our results, others Delp et al 2000) have shown previously that isolated arterioles from slow twitch muscle (i.e. the soleus) demonstrate a more potent vasodilatation in response to dilators acting through the vascular endotheliuni when compared to the response in isolated arterioles from fast twitch muscle (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…38 In the present study, we observed a decrease in systolic and MAP in the 6 weeks after SCI. In a previous deconditioning study in hindlimb unloaded rats, Delp at al 4 observed that reductions in transmural pressure induced atrophy of smooth muscle cells with no changes in vessel diameter. In addition, vascular adaptations to deconditioning with no changes in blood pressure were reported previously after 4 weeks of lower-limb suspension.…”
Section: Leg Volume and Blood Pressurementioning
confidence: 97%
“…Adaptations in vascular tone occur within days, whereas chronic and structural changes of the vessel wall are completed within 2 to 3 weeks. [3][4][5] In humans with longstanding SCI, extensive adaptations occur in the peripheral circulation such as a 30% decrease in diameter, a reduction in blood flow, and an almost doubling of stress levels in the femoral artery. 1,[6][7][8] Results on vascular changes derived from other models of deconditioning like bedrest studies [9][10][11] conflict with some studies showing a decrease in leg blood flow and others showing no changes after a period of bedrest varying from 10 to 41 days.…”
mentioning
confidence: 99%
“…In humans, impairments of macro-and microcirculation are also involved in this downregulation (1). On rodent models, studies were carried out and showed that simulated weightlessness has negative effects on structural (13) and functional properties (8,14) of vasculature. Another part of this downregulation is an alteration of equilibrium system (40).…”
Section: Why Countermeasure Had No Effect On Orthostatic Responsementioning
confidence: 99%